(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 1996)
Beliefs are necessary for living, but some are necessarily incongruous with others. Realisation of this might help us to be more understanding and sympathetic to those powerfully driven "To Know" what is more idiosyncratic, individualistic and mistaken. Existentialisms which emphasize existence rather than essences can encompass the issues, while much called Phenomenology is a symptom rather than a logical solution of the paradoxes involved. Intuition, and imagination are the basis of human creativity, but for different purposes they require social, pragmatic, psychological, and empirical confirmation. Confident assertion are only sometimes convincing, but repetition by enough of a society helps an ideology.